Structure-Function Relationships of the Follicle-Stimulating Hormone Receptor - Ulloa-Aguirre, Alfredo; Zariñán, Teresa; Jardón-Valadez, Eduardo; Gutiérrez-Sagal, Rubén; Dias, James A. (Frontiers in Endocrinology, 2018)
The follicle-stimulating hormone receptor (FSHR) plays a crucial role in reproduction. This structurally complex receptor belongs to the G-protein coupled receptor (GPCR) superfamily of membrane receptors. As with the other structurally similar glycoprotein hormone receptors (the thyroid-stimulating hormone and luteinizing hormone-chorionic gonadotropin hormone receptors), the FSHR is characterized by a large extracellular domain, where binding to FSH occurs, linked to the signal specificity subdomain or hinge region. This region is involved in ligand-stimulated receptor activation whereas the seven transmembrane domain is associated with receptor activation and transmision of the activation process to the intracellular loops comprised of amino acid sequences, which predicate coupling to effectors, interaction with adapter proteins, and triggering of downstream intracellular signaling. In this review, we describe the most important structural features of the FSHR intimately involved in regulation of FSHR function, including trafficking, dimerization and oligomerization, ligand binding, agonist-stimulated activation and signal transduction.